Condições de saúde bucal e acesso aos serviços de saúde bucal da população de 5 e 12 anos do município de Fortaleza-CE - Saldanha, Kátia de Góis Holanda (2021)
Epidemiological surveys in oral health are the main instruments of epidemiological research that generate primary data for the knowledge of the prevalence and typology of oral diseases. In this sense, the objective of this research was to determine oral health conditions, characterize the socioeconomic status of children aged 5 and 12 years in Fortaleza, Ceará, Northeast, and analyze access to dental services. This is a descriptive and cross-sectional study with children aged 5 and 12 years. A total of 4,729 children were examined by 30 dental surgeons, who participated in theoretical/practical training and Inter-examiner calibration. The final Kappa presented a value of 0.87. The examinations were performed using the clinical form adapted from the epidemiological survey SB Brasil 2010. Parents/guardians answered a questionnaire on socioeconomic characteristics, access to services and perception of oral health. . Data were analyzed using Pearson's chi-square test or Fisher's exact test, considering p<0.05. Variables showing p values <0.2 were included to a multinominal logistic regression model (forward stepwaise model). Values fitted into the model that present a significant difference had their odds ratios and 95% CI exposed. The research was approved by the Research Ethics Committee of the Universidade Federal do Ceará under opinion nº 3.092.816. It was observed that, at the age of 5 years, 57.1% of the children were free of caries, and the mean dmft was 1.65 (±2.65), with a predominance of the carious component (93 %) in its composition. No significant gingival changes were found and the presence of malocclusion was identified in 45.2% of the children. At the age of 12 years, it was observed that 67.3% of the children were free of caries and the mean DMFT was 0.86 (±1.52). The prevalence of fluorosis was 41.5% and 56.6% of the students did not present gingival bleeding and calculus in the examined sextants. Regarding the use of dental services, 51.8% of the children surveyed had already been to the dentist at some point in their lives. Children living in the Regional Health Coordination (CORES) V (OR=0.58), and a high number of people per household (OR=3.51) were less associated with the use of oral health services. Studying at a private school (OR=3.51) and owning a car were factors strongly associated with visits to the dentist. Considering good/optimal oral health (OR1.57), school absenteeism (OR=2.21), avoiding smiling (OR=2.70) and feeling pain (OR=1.99) were conditions associated with greater use of services. Speech impairment due to oral problems (OR=0.58) had a low association with service use. It is concluded that at ages 5 and 12 years, the city of Fortaleza has low caries severity and low prevalence of periodontal disease. Fluorosis is most prevalent in its very mild form. As for the severity of the malocclusions detected, malocclusion defined at 12 years of age prevailed, and mild malocclusions prevailed at the age of 5 years. Low access point to a picture of inequalities in oral health and the importance of planning actions considering social, economic and cultural factors in the choices of intervention proposals for the diseases studied.